Vibration Analysis and Experimental Study of GIS Busbar Enclosure under Electric Force - Dingge Yang; Yuzhao Li; Yanhua Han; Bin Ding; Liangshu Li; Jingfeng Wu (Shock and Vibration)
To explore the vibration response of the GIS busbar enclosure in a strong electric field, the electric force on the busbar enclosure was solved by the voltage in the circuit and the principle of virtual work. The vibration mode was obtained by finite element technology. Accordingly, the vibration response of the busbar enclosure was obtained by vibration analysis in the frequency domain, and the vibration acceleration of the busbar was monitored in the substation. The simulation results showed that the busbar enclosure was subjected to the electric force because of the fundamental voltage and harmonic voltages in the conductor. By coupling the radial electric force and the vibration mode, it was found that the vibration responses of the busbar enclosure at 100 Hz and 2900 Hz were greater than those at other frequencies. The experimental result showed that the frequency with the highest vibration amplitude was the same as that of the simulation result, and the vibration acceleration amplitude in the experiment and simulation at 2900 Hz was basically consistent, which verified the accuracy of the simulation result. The study shows that the GIS enclosure shell will produce vibration at the two times power frequency and high frequency, which provides an explanation for the high-frequency vibration of busbar shell structure in the ultra-high-voltage substation and provides an objective basis for the design of the busbar enclosure in the ultra-high-voltage substation.